Phenomenological Study Of Interpersonal Communication Among Online Game Players In The Indonesian Pubg Mobile Discord Community - M. Zufar Al Hilal; Diana Sari; Ashur Harmadi; Sabrina Rahma Utami; Rina Novianti (Jurnal Ilmiah Multidisiplin, 2025)
The phenomenon of online gaming has become an interesting aspect in Indonesian society, especially among Generation Z. Various groups and communities have formed around online games, with a special focus on PUBG Mobile. This study aims to uncover interpersonal communication patterns in the social interactions of online gamers in the Indonesian PUBG Mobile Discord community. By analyzing through the lens of symbolic interaction theory, this study adopts a qualitative method. Data were collected through observation, in-depth interviews, and documentation conducted with several key informants, in order to obtain relevant facts regarding the problems studied. The results of this study significantly indicate that social interaction and interpersonal communication in the context of this community go beyond the simple coordination function in the game. Both play a fundamental role as important elements in the formation and maintenance of strong social relationships among community members. The main motivation behind the behavior of social interaction and interpersonal communication between members is a deep desire to keep up to date with the latest developments in the PUBG Mobile game they play. The presence of personal and situational motivations collectively makes this community a conducive place, where good and mutually supportive relationships can be built and maintained among its members. This study highlights the multifaceted role of communication in online gaming communities, emphasizing its importance in fostering social cohesion, sharing interests, and creating a supportive environment for players.